2004
DOI: 10.1002/app.20407
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐screw extrusion compounding of polypropylene/organoclay nanocomposites modified by maleated polypropylenes

Abstract: Polypropylene/organoclay nanocomposites modified with different maleic anhydride grafted polypropylene (PPgMA) compatibilizers were compounded on a twin-screw extruder. The effectiveness of the feeding sequence and compatibilizer type toward the dispersion of organoclay into PP matrix was critically studied. The composites prepared with side feed appeared to provide better dispersion and modulus improvement over that with hopper feed. The effect of PPgMA compatibilizers, including PB3150, PB3200, PB3000, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol. There are some experimental studies suggesting the feasibility of the preparation of PNC from such polymers by melt compounding under selected process conditions, e.g., PP [14], poly[ethylene-co-(vinyl acetate)] (EVA) [15], PA-6 [13,16], etc. However, systematic studies of melt compounding of PNC are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol. There are some experimental studies suggesting the feasibility of the preparation of PNC from such polymers by melt compounding under selected process conditions, e.g., PP [14], poly[ethylene-co-(vinyl acetate)] (EVA) [15], PA-6 [13,16], etc. However, systematic studies of melt compounding of PNC are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…PP/MMTs are produced using many technologies, and their applications include a range of manufacturing processes at a relatively low cost [1,2] . There is much evidence that supports melting processing as the preferred production method of PP/MMT for commercial use [3][4][5][6][7] . Additionally, the literature suggests that the exfoliation and the dispersion of nanoclays in polypropylene requires the exchange of the sodium cations that are present in the nanoclay layers with the organophilic cations (dimethyl, dihydrogenated tallow, and quaternary ammonium chloride), which alters the initial interlayer spacing and improves the interaction between the clay and the PP [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of PP/organoclay nanocomposites [6][7][8] has drawn close attention from the researchers and engineers. However, the incompatibility and low interactions between hydrophobic PP and hydrophilic clay become very formidable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incompatibility and low interactions between hydrophobic PP and hydrophilic clay become very formidable. Recent studies [6,8] have shown that the use of functional maleic anhydride grafted PP (MAPP) as the compatibiliser can improve the clay dispersion with more effective intercalated structures.…”
Section: Introductionmentioning
confidence: 99%